Prarancangan Eco-Efficiency Pabrik Nanokitosan dari Cangkang Kepiting Kapasitas 31.868 ton/tahun - , BOBBY NUGROHO WICAKSONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The basic concept of this plant is originated with the idea of Blue Economy, which aims to optimally use the local resources to develop self-sufficiency and fair trades. The commodity to be processed is the crab shell wastes, as an important part of the potential marine-based business. The crab shell is converted into chitosan, which will be sold in two forms: 1) as the suspension of nano-chitosan for preservation agent (as \"society-oriented product \" sold at very low prices as the plantâs social outreach to the surrounding community), 2) as pharmaceutical grade chitosan powder (as a \"commercial product\" sold at high price to guarantee the plant profitability). The process takes ground shell crab ( 50 mesh ) as raw materials. Firstly, chitin is isolated from the shell crab. Chitin isolation process consists of deproteination (82.57 % conversion) and demineralization process (99.08 % conversion). Conversion of chitin into chitosan and nano-chitosan consists of deacetylation and the production of nano-chitosan suspension. The reactants used are NaOH solution (in the deproteination and deacetylation reactor) and HCl solution (in demineralization reactor). The plant scheduling is based on Gant Chart optimum system, where the total cycle time consisted of charging, processing, emptying, and cleaning. The time for deproteination, demineralization, and deacetylation reactor is 0.83 hours, 13.33 hours, and 6.67 hours respectively. The production of nano-chitosan is based on pH adjustment, whereby the pH of chitosan dissolved in 1.50% acetic acid solution is gradually raised upto very close to its isoelectric pH (6.5). The process is carried out by slowly adding the residual NaOH solution from deacetylation process. The plant is designed with the capacity of 31.868 tons/year for nanochitosan and 1.607 ton/tahun for chitosan powder. This plant also produce crude amino acid as side product with capacity 914 ton/year. All of products are produced from crab shell as much as 10.610,53 tons/year, CH3COOH 99% as much as 542,05 tons/year, NaOH solid as much as 5744,34 tons/year and HCl 33% as much as 18.286,24 tons/year. Utilities includes water as much as 76,22 tons/hour